Streptococcus pneumoniae - an uncommon cause of neonatal sepsis: two case reports - GCS Gunasekera; GPS Gunaratna; R Sathanantharajah; NS Chandrasiri (Sri Lankan Journal of Infectious Diseases, 2022)
Streptococcus pneumoniae is a rare but recognized aetiological agent for neonatal sepsis. In the context of scarce local data, we report two cases of early-onset neonatal sepsis (EONS) due to pneumococci that probably occurred following ascending transmission during the perinatal period.